Indy Mutations and Drosophila Longevity - Rogina, Blanka; Helfand, Stephen L. (Frontiers in Genetics, 2013)
Decreased expression of the fly and worm Indy genes extends longevity. The fly Indy gene and its mammalian homolog are transporters of Krebs cycle intermediates, with the highest rate of uptake for citrate. Cytosolic citrate has a role in energy regulation by affecting fatty acid synthesis and glycolysis. Fly, worm and mice Indy gene homologues are predominantly expressed in places important for intermediary metabolism. Consequently, decreased expression of Indy in fly and worm, and the removal of mIndy in mice exhibit changes associated with calorie restriction, such as decreased levels of lipids, changes in carbohydrate metabolism and increased mitochondrial biogenesis. Here we report that several Indy alleles in a diverse array of genetic backgrounds confer increased longevity.